Rel Ganda dan Program Sosial: Harapan dan Tantangan Warga di Era Pembangunan - Haikal Primsa Ginting; Muhammad Aqsha Rangkuti; Sanreza Pallevi Malau; Hairani Siregar (Penerbit Jurnal Indonesia, 2024)
The construction of a double-track railway in KaptenMuslim, Medan, aims to improve connectivity and support local economic growth. This rail-based transportation infrastructure is considered capable of reducing congestion and accelerating the distribution of goods and community mobility. This study uses a qualitative method with a descriptive approach, collecting data through semi-structured interviews and participant observation in the affected environment. The findings show that this project opens up new economic opportunities, especially for small traders and local transportation service providers. However, challenges such as congestion during construction, noise impacts, and the need for fair compensation are major concerns for the community. Mitigating social impacts through policies and active involvement of local communities is considered important to ensure the sustainability of the benefits of this project.